Improved electrochemical kinetics and rate performance of lithium-ion batteries by Li2FeS2−xFx cathode materials - Adane Gebresilassie Hailemariam; Mohammad Qorbani; Tadios Tesfaye Mamo; Raghunath Putikam; Chih-Yang Huang; Khasim Saheb Bayikadi; Heng-Liang Wu; Ming-Chang Lin; Li-Chyong Chen; Kuei-Hsien Chen (Communications Materials)
Abstract Lithium iron sulfide (Li2FeS2) exhibits unique characteristics, including multielectron redox behavior and abundant valence states, making it a promising candidate for electrode material in lithium-ion batteries. However, the sluggish charge transfer kinetics, low stability, and slow rate performance hamper its practical application. Herein, we propose a strategy to boost the electrochemical performance of Li2FeS2 by substituting F dopants with S sites through a two-step solid-state process. The effects of F dopants on material characteristics and electrochemical behaviors are investigated. Experimental results show that F dopants significantly enhance diffusion kinetics and rate performance, indicating improved interfacial activity in Li2FeS2−xFx. Theoretical calculations confirm that F substitution occurs at the S site, enhancing charge mobility. After 100 cycles, the optimized Li2FeS2-xFx cathode exhibits a specific capacity of 250 mAh g−1, higher than pristine Li2FeS2. The improved electrochemical properties, diffusion kinetics, capacity, and rate performance are attributed to the enhanced structural stability from a stronger metal–fluorine bond compared to metal–sulfur, and increased Li+ ion diffusion due to a greater electronegativity difference.